Chemical Analyses of Archaeological Bone-Samples: Evidence for High Lead Exposure on the Faroe Islands - Nielsen, Ole Vagn; Grandjean, Philippe; Bennike, Pia (Journal of Danish Archaeology, 1982)
Chemical Analyses of Archaeological Bone-Samples: Evidence for High Lead Exposure on the Faroe Islands.